Timing and causes of North African wet phases during the last glacial period and implications for modern human migration - Hoffmann, Dirk L.; Rogerson, Michael; Spötl, Christoph; Luetscher, Marc; Vance, Derek; Osborne, Anne H.; Fello, Nuri M.; Moseley, Gina E. (Scientific Reports, 2016)
We present the first speleothem-derived central North Africa rainfall record for the last glacial period. The record reveals three main wet periods at 65-61ka, 52.5-50.5ka and 37.5-33ka that lead obliquity maxima and precession minima. We find additional minor wet episodes that are synchronous with Greenland interstadials. Our results demonstrate that sub-tropical hydrology is forced by both orbital cyclicity and North Atlantic moisture sources. The record shows that after the end of a Saharan wet phase around 70ka ago, North Africa continued to intermittently receive substantially more rainfall than today, resulting in favourable environmental conditions for modern human expansion. The encounter and subsequent mixture of Neanderthals and modern humans – which, on genetic evidence, is considered to have occurred between 60 and 50ka – occurred synchronously with the wet phase between 52.5 and 50.5ka. Based on genetic evidence the dispersal of modern humans into Eurasia started less than 55ka ago. This may have been initiated by dry conditions that prevailed in North Africa after 50.5ka. The timing of a migration reversal of modern humans from Eurasia into North Africa is suggested to be coincident with the wet period between 37.5 and 33ka.